Research on plant characteristics and application strategies for the planning and design of herbal gardens - Lin, Xiaohua; Wu, Zhaocheng; Liu, Junmin; Gao, Liwen; Zhan, Ruoting (Frontiers in Plant Science, 2025)
Herbal gardens have a long history worldwide and serve important functions in education, science popularization, cultural dissemination, tourism, and convalescence. In recent years, growing interest in health, nature, and culture has led numerous institutions to establish herbal gardens of various scales. However, standardized research on the planning and design of herbal gardens is still lacking, especially regarding species selection, planting layout, and the exploration and functional utilization of medicinal plant properties. This study conducted a detailed analysis of over 1,000 medicinal plant species in the Herbal Garden of Guangzhou University of Chinese Medicine, focusing on taxonomy, plant habit types, ecological habits, aromatic and ornamental characteristics, medicinal functions, edible properties, and cultural significance. Based on this analysis, the study proposed design principles rooted in ecological diversity, health and safety, and practical functionality, and proposed context-specific, characteristic-driven garden planning to maximize the educational, therapeutic, and public outreach potential of herbal gardens. The findings aim to provide theoretical and practical guidance for the planning and design of diverse types of herbal gardens.